FinTech, financial inclusion, and green growth in ASEAN-5 countries: evidence from multidimensional panel analysis methods - Demirkale, Ozge; Duran, Naime Irem; Han, Ayşegül; Seyranlioglu, Onur (Frontiers in Applied Mathematics and Statistics, 2025)
This study aims to examine the effects of FinTech development and financial inclusion on green growth in ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) over the period 1995–2023. Using PMG, Panel FMOLS, and Panel DOLS estimators alongside wavelet coherence analysis, we investigate both the individual and interaction-based impacts of FinTech and financial inclusion. PARDL-PMG, Panel DOLS and Panel FMOLS results indicate that FinTech development and financial inclusion each exert a significant positive effect on green growth. At the same time, their interaction term highlights the complementary benefits of an inclusive digital financial (DF) ecosystem. Dumitrescu–Hurlin causality tests confirm a bidirectional relationship between green growth and the FinTech–inclusion interaction, as well as a unidirectional causality running from FinTech to green growth. Wavelet coherence analyses reveal particularly strong time–frequency co-movement patterns in Singapore, Indonesia, and the Philippines. Overall, the results suggest that digital financial ecosystems can support green growth, provided that targeted policies address structural asymmetries. This study fills a gap in the literature as the first comprehensive analysis of the long-run, time–frequency effects of the FinTech–financial inclusion interaction in the ASEAN-5 region. Given the contribution of digital financial systems to green growth, it is essential that policymakers develop inclusive, coherent, and structurally sensitive digital finance policies in order to fully realize this potential. These findings imply that policymakers should design inclusive digital-finance frameworks that balance innovation with sustainability.JEL ClassificationO16, Q56, G21, C33.